Social interaction and the quality of the learning environment have an impact on the language development of young children at TKIT Ulul Albaab. - Maimunah; Priyanti, Nita (Kirana Publisher (KNPub), 2024)
This study aims to analyze the influence of social interaction and the quality of the learning environment on children's language development at TKIT Ulul Albaab. Employing a quantitative approach with a survey method, this research applies a correlational design to investigate causal relationships between variables. The research population includes all students aged 4-6 years at TKIT Ulul Albaab, with a total sampling of 59 children as respondents. Data collection was conducted through structured observations using instruments that have been tested for validity and reliability. Data analysis utilized multiple linear regression. The results show: (1) there is a significant influence of social interaction on children's language development (R² = 0.774, sig. 0.001), (2) there is a significant influence of learning environment quality on children's language development (R² = 0.545, sig. 0.003), and (3) there is a significant joint influence of social interaction and learning environment quality on children's language development (R² = 0.733, sig. 0.005). In conclusion, social interaction and the quality of the learning environment play crucial roles in supporting early childhood language development, with social interaction having a more dominant influence. The research implications emphasize the importance of enhancing the quality of social interactions and learning environments to optimize children's language development in early childhood education institutions.